The apoptotic analysis of 7α-hydroxy-β-sitosterol extracted from Chisocheton tomentosus (Meliaceae) in cancer cell lines / Mohammad Tasyriq bin Che Omar - Che Omar, Mohammad Tasyriq (2012)
The main objective of the present study is to investigate the cytotoxicity potential and anti-cancer mechanism of 7α-hydroxy-β-sitosterol (CT1), a known stigmastane sterol extracted from bark of Chisocheton tomentosus (Meliaceae). In vitro exposures of this compound was conducted on five cancer cell lines; breast adenocarcinoma cells (MCF-7), hepatocyte liver carcinoma cell (HepG2), oral squamous carcinoma cell (HSC-4) and (HSC-2) and epidermoid cervical carcinoma (Ca Ski) and in comparison with normal human mammary epithelia cell line (HMEC). Cell viability was assessed by the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay and Live/Dead cytotoxic/viability assay. The flow cytometric analysis and DNA fragmentation assays were used to determine mode of cell death mediated by CT1. Wound healing assay was performed to investigate the potential of migration inhibitory effect of CT1. Protein levels were examined by Western blot analysis. The results demonstrated that CT1 exposure markedly cytotoxic toward MCF-7, HepG2 and HSC-4 cells in time- and dose-dependent manner. Conversely CT1 did not significantly affect the viability of HSC-2, Ca Ski and HMEC cells within a similar dosage range. In vitro scratch assay showed the potential of CT1 to inhibit migration of HSC-4 cells without significant effect observed for MCF-7 and HepG2 cells. Flow cytometric analysis for annexin V/PI dual staining demonstrated that death was achieved via apoptosis followed by secondary necrosis after 24 h post-treatment period at IC50 concentrations. Apoptotic effects of CT1 were confirmed by DNA fragmentation which showed laddering of DNA for three tumor cell lines without forming significant laddering in HMEC cells. Cell cycle analysis also demonstrated that CT1 caused an accumulation in the G0/G1-phase of cell cycle in MCF-7 cells. Western blotting analysis on apoptotic proteins lysed from MCF-7 cells treated with CT1 suggested that induction of MCF-7 cell death via apoptosis was modulated through both intrinsic and extrinsic pathway. A time-dependent up regulation of Bax/Bcl protein ratio, Fas Ligand and procaspase 8 proteins and down regulation of procaspase 9, procaspase 3, procaspase 6, Bim and ERK 1/2 proteins were detected in MCF-7 cells confirmed the pathway. In conclusion, CT1, a natural compound from the Malaysian plant exhibited its potential use as a cancer chemopreventive agent.